China's monetary policy and the exchange rate - Aaron Mehrotra; José R. Sánchez-Fung (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
The paper models monetary policy in China using a hybrid McCallum-Taylor empirical reaction function. The feedback rule allows for reactions to inflation and output gaps, and to developments in a trade-weighted exchange rate gap measure. The investigation finds that monetary policy in China has, on average, accommodated inflationary developments. But exchange rate shocks do not significantly affect monetary policy behavior, and there is no evidence of a structural break in the estimated reaction function at the end of the strict dollar peg in July 2005. The paper also runs an exercise incorporating survey-based inflation expectations into the policy reaction function and meets with some success.
URN:NBN:fi:bof-201408071938
Keywords: 330